Premutation Females with preFXTAS - Liani, Valentina; Torrents, Carme; Rolleri, Elisa; Yusoff, Nor Azyati; Likhitweerawong, Narueporn; Moore, Sydney; Tassone, Flora; Schneider, Andrea; Santos, Ellery; Biag, Hazel M. B.; Bourgeois, James A.; Unruh, Kathryn E.; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Fragile-X-associated tremor/ataxia syndrome (FXTAS) is a progressive neurodegenerative disorder associated with the FMR1 gene premutation, characterized by the presence of 55 to 200 CGG triplet repeat expansions. Although the initial symptoms of FXTAS typically manifest in males around the age of 60 with motor symptoms and cognitive deficits, the presentation and progression in females differ. Women, in fact, exhibit a higher prevalence of neuropsychiatric symptoms, with an earlier onset compared to the motor symptoms observed in men. The following article reports on ten cases of women with a diagnosis of FMR1 gene premutation, originating from two medical centers. All the women in the study exhibited neuropsychiatric symptoms and subtle neurological signs as common features. Symptoms typically observed in the male population, such as tremors and cerebellar ataxia, were either absent or significantly reduced in the female cohort. Conversely, there was a higher prevalence of neuropsychiatric symptoms among the women. Neurocognitive impairment was only minimally evident, with mild executive dysfunction and memory complaints noted in a subset of cases. For this reason, we propose the terminology preFXTAS or prodromic FXTAS to define a clinical presentation in women characterized by early manifestations of FXTAS that do not entirely fulfill the established diagnostic criteria but exhibit MRI evidence of white matter alterations suggesting the initiation of the disease process. The study underscores the importance of establishing new diagnostic criteria for FXTAS and, at the same time, developing new biomarkers and interview checklists/assessment scales dedicated to females.